Values of females and males in the east and west: Are they similar or different? - Uy, Arnel Onesimo O. (Animo Repository, 2010)
Understanding whether cross-cultural values are similar or different has become more important in an increasingly global marketplace. Yet, few studies have explored cross-cultural sex-based value structures. This study examines the values of 5,134 male and female working adults in three Eastern nations (Japan, the Philippines, and Thailand) and three Western nations (United States, United Kingdom, and Iceland). For similarities, males and females more highly valued personal than social terminal values. For differences, males in the East more highly valued self-actualization/competence instrumental values. Females in both geographic groups placed higher importance on social terminal values than did males, supporting prior research. © 2010 De La Salle University, Manila, Philippines.